Forecasting the intraday market price of money - Andrea Monticini; Francesco Ravazzolo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
Central banks' operations and efficiency arguments would suggest that the intraday interest rate should be set to zero. However, a liquidity crisis introduces frictions related to news, which can cause an upward jump of the intraday rate. This paper documents that these dynamics can be partially predicted during turbulent times. Long memory approaches or a combination of them to account for model uncertainty outperform random walk, autoregressive and moving average benchmarks in terms of point and density forecasting. The relative accuracy is higher when the full distribution is predicted. We also document that such statistical accuracy can provide economic gains in investment strategies based on lending in the intraday market.
Keywords: C22; C53; E4; E5; 330; interbank market; intraday interest rate; forecasting; density forecasting; policy tools